2020
DOI: 10.3892/mmr.2020.11323
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑199a‑5p suppresses cell proliferation, migration and invasion by targeting ITGA3 in colorectal cancer

Abstract: as a member of the integrin family, integrin α3β1 (iTGa3) has been linked to intercellular communication and serves an important role in the signaling among cells and the extracellular matrix. Microrna (mir)-199a-5p has been demonstrated to be related to the pathogenesis and progression of multiple malignant diseases. However, the biological functions of mir-199a-5p and iTGa3 in colorectal cancer (crc) have rarely been reported. The aim of the present study was to explore the roles of mir-199a-5p and iTGa3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
(40 reference statements)
2
18
0
Order By: Relevance
“…In this study, the ECM-receptor interaction was substantially enriched in 3 DEMs, including ITGA3, ITGA4 , and COL4A5 . These three genes were more closely related to diseases ( 64 66 ), but studies have found that ITGA3, ITGA4 , and COL4A1 may be involved in the composition of adipocyte extracellular matrix and the differentiation of adipocytes ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ECM-receptor interaction was substantially enriched in 3 DEMs, including ITGA3, ITGA4 , and COL4A5 . These three genes were more closely related to diseases ( 64 66 ), but studies have found that ITGA3, ITGA4 , and COL4A1 may be involved in the composition of adipocyte extracellular matrix and the differentiation of adipocytes ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…An image of each scratch was captured under a light microscope. Subsequently, cells were incubated in RPMI-1640 medium containing 1% FBS (26). After culturing for 24 h at 37˚C, images of the scratches were captured again.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Our chosen target inhibits proliferation, migration, and invasion in colorectal cancer by negatively regulating integrin α3β1 (ITGA3), which has been linked to intercellular communication and serves an important role in the signaling among cells and the extracellular matrix. In addition, it was suggested that miR-199a-5p overexpression suppresses the EMT of colorectal cancer cells, whereas the overexpression of ITGA3 restores this effect [ 137 ]. The same holds true by looking at another miR199a-5p direct target, ROCK1 (Rho-associated coiled coil-containing protein kinase 1), Zhu and colleagues demonstrated in their study that microRNA-199a-5p was significantly downregulated in colorectal cancer cell lines and tissue samples and was associated with a poor prognostic phenotype.…”
Section: Discussionmentioning
confidence: 99%